Structural Influence of Lone Pairs in GeP2N4, a Germanium(II) Nitridophosphate. Issue 3 (8th December 2022) - Ambach, Sebastian J.; Somers, Cody; de Boer, Tristan; Eisenburger, Lucien; Moewes, Alexander; Schnick, Wolfgang
Abstract: Owing to their widespread properties, nitridophosphates are of high interest in current research. Explorative high‐pressure high‐temperature investigations yielded various compounds with stoichiometry M P2 N4 ( M =Be, Ca, Sr, Ba, Mn, Cd), which are discussed as ultra‐hard or luminescent materials, when doped with Eu 2+ . Herein, we report the first germanium nitridophosphate, GeP2 N4, synthesized from Ge3 N4 and P3 N5 at 6 GPa and 800 °C. The structure was determined by single‐crystal X‐ray diffraction and further characterized by energy‐dispersive X‐ray spectroscopy, density functional theory calculations, IR and NMR spectroscopy. The highly condensed network of PN4 ‐tetrahedra shows a strong structural divergence to other M P2 N4 compounds, which is attributed to the stereochemical influence of the lone pair of Ge 2+ . Thus, the formal exchange of alkaline earth cations with Ge 2+ may open access to various compounds with literature‐known stoichiometry, however, new structures and properties. Abstract : With the discovery of the first germanium(II) nitridophosphate, GeP2 N4, we present a way to use the stereochemical influence of lone pairs to modify crystal structures. This approach could be applied to other literature‐known nitridophosphates by cation exchange, altering the crystal structures and thus further increasing their already widespread properties and field of application.